The adventures of Marco Flamingo under the sea = Las aventuras submarinas de Marco Flamenco - Jarkins, Sheila (Raven Tree Press, 2009)
Marco lives in a calm lagoon. Far off in the distant, he sees the waves of the ocean and decides to visit. While Marco explores the ocean, he meets many new friends.